2016
DOI: 10.1111/jace.14351
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Oxygen Activity Conditions on the Phase Equilibria and Cation Occupancy of Strontium Barium Niobate

Abstract: Strontium barium niobate (SBN) is a tungsten bronze family ferroelectric which shows promising thermoelectric properties under reducing conditions. It is found here that the enhanced electrical conductivity of oxygen‐deficient SBN correlates with the formation of a NbO2 secondary phase. The effects of the reducing environment and the NbO2 phase formation are studied via a detailed defect chemistry analysis. Increasing amounts of the NbO2 phase are accompanied by an interesting mechanism where the A‐site occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…10 The large increase in conductivity was associated with the filling of the A-site vacancy in the structure, and the resulting generation of carriers. 9,11,12 Here, the filling of the A-site acts as the other source of dopants. With respect to unfilled SBN, the effect of the A-site occupancy can be demonstrated with the expression:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The large increase in conductivity was associated with the filling of the A-site vacancy in the structure, and the resulting generation of carriers. 9,11,12 Here, the filling of the A-site acts as the other source of dopants. With respect to unfilled SBN, the effect of the A-site occupancy can be demonstrated with the expression:…”
Section: Introductionmentioning
confidence: 99%
“…12 The filling of the A-sites was supported by the observation that NbO 2 precipitation was reversible, showing that neither Ba nor Sr were volatilizing out of the system. 11 For unfilled SBNs, the amount of NbO 2 precipitated (which is a function of pO 2 and temperature) controlled the degree of A-site occupancy. 11 It was found that 100% A-site occupancy could not be reached in unfilled SBN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 TB niobate oxides with general formula of (A1) 4 (A2) 2 (C) 4 Nb 10 O 30 are based on ab-planar array of corner-shared NbO 6 octahedrons that are stacked along the c-axis to form different tunnels with pentagonal (A1), quadrangular (A2), and triangular (C) cross-sections in the crystal lattice. [5][6][7][8][9][10][11] In addition, niobate materials with the 'filled' TB structure usually exhibit much better dielectric and ferroelectric properties compared to those with the 'unfilled' TB structure. 4 It is reported that the distortion of NbO 6 octahedral polar unit can be greatly affected by the ion-occupying-situation, ionic size, and electronegativity of substituted ions, resulting in some special dielectric and ferroelectric behaviors in TB niobate materials.…”
Section: Introductionmentioning
confidence: 99%
“…4 It is reported that the distortion of NbO 6 octahedral polar unit can be greatly affected by the ion-occupying-situation, ionic size, and electronegativity of substituted ions, resulting in some special dielectric and ferroelectric behaviors in TB niobate materials. [5][6][7][8][9][10][11] In addition, niobate materials with the 'filled' TB structure usually exhibit much better dielectric and ferroelectric properties compared to those with the 'unfilled' TB structure. 5,8,12 In the past decades, luminescent-ferroelectic materials have aroused considerable attention as that they can be developed for future multifunctional optoelectronic devices within a single material.…”
Section: Introductionmentioning
confidence: 99%